If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11=u/2-13
We move all terms to the left:
11-(u/2-13)=0
We get rid of parentheses
-u/2+13+11=0
We multiply all the terms by the denominator
-u+13*2+11*2=0
We add all the numbers together, and all the variables
-1u+48=0
We move all terms containing u to the left, all other terms to the right
-u=-48
u=-48/-1
u=+48
| (x-10)+12=-38 | | 6x-11=3x+5 | | 4x+5x=50+22 | | 3z=z+221/2 | | 4/5=x+3/5 | | -q+5.8=23.8 | | 6(2)+4x=40 | | 3y+5y+12=36 | | 3x+5=6x-11 | | 9(z+2)-(5z-8)=3z | | y/4-12=18 | | x/5=8/7 | | -2x–7=-9 | | 3x–9=0 | | 31=y/2+16 | | 5(0.75)^x=2 | | 10-2x-12+7x=20x+10=17x | | (x-3÷5)-2=2x÷5 | | 6(2x–5)+3=57x= | | 3m=2=-10 | | -3=t/6 | | 11+6x=3x-13 | | 24=5w-11 | | 3z=1/2(z+22) | | 10-5=21-3x* | | 2s=2(-6) | | 3z=1/2z+22 | | 24s=24(-6) | | X+3(x+4)=30 | | -2(y+12)=y9 | | 26z=910 | | -17+(n/5)=33 |